2022
DOI: 10.1159/000522432
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and the Endocannabinoid System: Smart Lipids – A Novel Therapeutic Option?

Abstract: The development of a high-end cannabinoid-based therapy is the result of intense translational research, aiming to convert recent discoveries in the laboratory into better treatments for patients. Novel compounds and new regimes for drug treatment are emerging. Given that previously unreported signaling mechanisms for cannabinoids have been uncovered, clinical studies detailing their high therapeutic potential are mandatory. The advent of novel genomic, optogenetic, and viral tracing and imaging techniques wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 135 publications
(166 reference statements)
0
7
0
1
Order By: Relevance
“…Thus, the MEPIRAPIM backbone might offer a viable new chemotype to develop T-type channel inhibitors lacking cannabimimetic activity. Notwithstanding this, it is conceivable that dual T-type and cannabinoid receptor activity may enhance therapeutic effects, particularly in pain and epilepsy models in which both are relevant targets ( Roebuck et al, 2021 ; Anderson et al, 2022 ; Sugaya and Kano, 2022 ; Zieglgänsberger et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the MEPIRAPIM backbone might offer a viable new chemotype to develop T-type channel inhibitors lacking cannabimimetic activity. Notwithstanding this, it is conceivable that dual T-type and cannabinoid receptor activity may enhance therapeutic effects, particularly in pain and epilepsy models in which both are relevant targets ( Roebuck et al, 2021 ; Anderson et al, 2022 ; Sugaya and Kano, 2022 ; Zieglgänsberger et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the complexity of the aforementioned systems and their interactions. However, a detailed description of such systems is beyond the scope of this review and can be found elsewhere [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Objectivesmentioning
confidence: 99%
“…There are various conditions where chronic pain results in chronic stress and anxiety, and these may be ameliorated by treatments involving endocannabinoid signaling [164,165]. One option would be the application of naboxilols or cannabis preparations high in cannabidiol content, which lack the anxiogenic effects of ∆9-THC [166]. Other cannabinoid signaling-related treatments are also applicable (see Section 3.3).…”
Section: Cb1 Receptor Pharmacologymentioning
confidence: 99%